FET578 : Ceramic dimension art and idea (pilihan 3D) / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This module provides students with a deeper understanding of ideas, materials and ceramic processes. More comprehensive experiments will be conducted in exploring ideas through materials and processes.. Exercises include experimental techniques, wheel work, model and mould making, slip casting, surface treatments and glaze (colours) making. Student will be guided through various set projects and supported with series of lectures and group critic sessions in studio practice. Projects set will deal with a more complex forming problems and all elements and principle of forms, ideas and execution/experiments. At the end of the semester student will present (display and oral presentation) their complete art work for evaluation.